Keeping kids sun safe: Exploring parents' beliefs about their young child's sun-protective behaviours - Hamilton, Kyra; Cleary, C.; White, K.; Hawkes, A. (Wiley InterScience, 2016)
Objectives: Melanoma of the skin is the third most commonly diagnosed cancer in Australia. Given the high incidence of sunburn in children and the level of sun protection provided by parents is often infrequent and/or insufficient, this research employed qualitative methodology to examine parents' beliefs about their young child's sun safe behaviour. Methods: Parents (N = 21; n = 14 mothers, n = 7 fathers) of children aged 2-5 years participated in focus groups to identify commonly held beliefs about their decision to sun protect their child. Data were analysed using thematic content analysis. Results: Parents generally had knowledge of the broad sun safe recommendations; however, the specific details of the recommendations were not always known. Parents reported adopting a range of sun-protective measures for their child, which depended on the time of year. A range of advantages (e.g. reducing the risk of skin cancer, developing good habits early and parental peace of mind), disadvantages (e.g. false sense of safety and preventing vitamin D absorption), barriers (e.g. child refusal) and facilitators (e.g. routine and accessibility) to performing sun safe practices were identified. Normative pressures and expectations also affected parents' motivation to be sun safe for their child. Conclusions: These identified beliefs can be used to inform interventions to improve sun safe behaviours in young children who reside in a region that has the highest skin cancer incidence in the world.